Nilai-Nilai Wawasan Kebangsaan pada Buku Ajar Bahasa Indonesia bagi Mahasiswa di Perguruan Tinggi Agama Islam - Alfiati Alfiati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
This study aims to analyze textbooks for general Indonesian language courses that contain national insight in Islamic Higher Education Institutions throughout the Madiun Residency. The data collection process was carried out in five Islamic higher education institutions and used observation and interview methods with lecturers and students. From this study, data was obtained that lecturers still use textbooks printed on the market and have not used textbooks written by lecturers. There is an instillation of national values ​​in textbooks used in Indonesian language courses. In the process of instilling national values ​​in textbooks for general Indonesian language courses, it is reflected in the material on history, position, and function of Indonesian language. Supporting factors in instilling national values ​​include the existence of practices and assignments in learning general Indonesian language courses. Inhibiting factors in instilling national values ​​include the fact that there are still general Indonesian language course books that do not contain national insight. To overcome obstacles in instilling national values ​​and diversity in lecturers, teachers increase references in the use of textbooks in general Indonesian language courses for student teaching materials.